Civil Society Is the Second Pillar of West African Nation States - Poulton, Robin E. (Social Inquiry: Journal of Social Science Research, 2020)
Experience from many African nations – as well as America, Asia and Europe – provides compelling evidence that civil society plays a fundamental role in social progress and in promoting peace and democratic governance. Civil society has organised democratic governance in West African for millennia, and not simply since colonial rule began. Our political science research shows how civil society has been and remains critical to the evolution of West African Nation States – nearly all of which are recent post-colonial creations – and that a Five Pillar conception of the Nation State conforms more closely to West African realities than the traditional Western concept of Executive + Legislative + Judiciary. We propose that Civil Society and the Military should be added to the traditional State Pillars used in American and European analyses, since both have been - and remain - vital actors in the construction of West African Nation States since the 1960s. Moreover, civil society is often able to exert “countervailing power” - an expression coined by Professor J. K. Galbraith (1952) that puts pressure on the West African Executive, Legislature, Judicial and the Military pillars to help them function more effectively. It is civil society (sometimes with support from the nebulous “international community”) that keeps the other four pillars operating within their appropriate roles. This places civil society in the second place, after the Executive pillar.